2005
DOI: 10.1111/j.1471-4159.2005.03460.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E is required for normal synaptic transmission from photoreceptors to the inner retina

Abstract: Defects in the gene encoding carboxypeptidase E (CPE) in either mouse or human lead to multiple endocrine disorders, including obesity and diabetes. Recent studies on Cpe-/-mice indicated neurological deficits in these animals. As a model system to study the potential role of CPE in neurophysiology, we carried out electroretinography (ERG) and retinal morphological studies on Cpe-/-and Cpe fat/fat mutant mice. Normal retinal morphology was observed by light microscopy in both Cpe-/-and Cpe fat/fat mice. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…We initially characterized the CPE KO mouse with respect to its most obvious phenotypes: obesity, diabetes, and infertility (7). Other studies on CPE KO mice have shown defective secretion of mature brain-derived neurotrophic factor (BDNF) in the hippocampus (26), defective secretion of glutamate in the retina (40), specific neuronal degeneration in the CA3 region of the hippocampus (36), and defective dendritic pruning and spine formation of layer V cortical neurons (6,35). Thus CPE appears to play a role, either directly or indirectly, in many processes both inside and outside the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…We initially characterized the CPE KO mouse with respect to its most obvious phenotypes: obesity, diabetes, and infertility (7). Other studies on CPE KO mice have shown defective secretion of mature brain-derived neurotrophic factor (BDNF) in the hippocampus (26), defective secretion of glutamate in the retina (40), specific neuronal degeneration in the CA3 region of the hippocampus (36), and defective dendritic pruning and spine formation of layer V cortical neurons (6,35). Thus CPE appears to play a role, either directly or indirectly, in many processes both inside and outside the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vertebrates and invertebrates have demonstrated that CPE is required for neurotransmission. [84][85][86] Cell biological studies in CPE-knockout mice demonstrated that loss of CPE leads to significant reductions of synaptic vesicles docked at active zones. This phenotype, which is similar to that of synapsin knockouts, was not the result of decreased synaptic protein levels or of defects in synaptic vesicle biogenesis.…”
Section: F-actin Is Required For Proper Development Of the Presynaptimentioning
confidence: 99%
“…[15][16][17] The Nrl Ϫ/Ϫ and Nrl Ϫ/Ϫ Grk1 Ϫ/Ϫ mice maintained in total darkness, ambient (ϳ5 lux) cyclic light, or bright (ϳ8000 lux) constant light were recorded at 1, 3, 5, 7, and 9 months of age. At least 10 mice were recorded for each genotype at each age.…”
Section: Electroretinographymentioning
confidence: 99%